One-year descriptive analysis of patients treated at an anti-rabies clinic—A retrospective study from Kashmir - Bashir, Khalid; Haq, Inaamul; Khan, S. Muhammad Salim; Qurieshi, Mariya Amin (PLOS Neglected Tropical Diseases, 2020)
Author summary In Kashmir, dog bite is an important public health problem. Thousands of people become victims of an animal bite, especially dog bite, and some of them develop rabies. Rabies is an invariably fatal viral disease resulting in approximately 59 000 human deaths per year globally, with 95% of cases occurring in Africa and Asia. The only way to prevent a rabies death is vaccination of an animal bite victim. In Kashmir, the burden and characteristics of dog bites are not routinely captured by the health system in place. We, therefore, attempted to find out the burden and characteristics of animal bite victims by analyzing one-year data from an Anti-Rabies Clinic at a tertiary care hospital in Kashmir. We found that 98% of the patients registered at the clinic during the period were victims of a dog bite. The victims were mostly young males but females and children were not shown any mercy either. Lower limbs were the most frequently reported site of the bite. Our analysis of the data also revealed that children under 15 years were more prone to a bite in the head and neck region. We concluded that the burden of animal bites, especially dog bites, is high in Kashmir and recommended that serious efforts need to be put into practice to decrease the number of animal bite victims and prevent any rabies deaths.